UPAYA MENINGKATKAN KEMAMPUAN BERBICARA PADA PEMBELAJARAN BAHASA ARAB MELALUI METODE ROLE PLAYING (BERMAIN PERAN) - Davik (Lughoti (Jurnal Pendidikan Bahasa Arab) Jurnal program studi PBA, 2021)
Learning is a process of giving learners in order to have the ability or skills. In learning Arabic Language. It requires an innovative learning techniques and creative so that learners have the competence to speak in the language of Arabic. Learning Arabic languange for this is still a teacher-centered learning, many teachers argue in front of the class. Meanwhil, children just sit and listen to what is being said by the teacher. In addition, teachers often use methods that are less appropriate to the material so it does not stimulate the students' speaking skills. Children are not given the opportunity to express what children know to talk and tell stories in front of the class. In addition, speech development still need to be developed further. Children are still embarrassed to come forward in front of the class and reveal what children know. Based on these problems, the importance of learning application that is fun and more significance in conveying a concept on Arabic learning. Role play is one of the techniques of learning with communicative strategies. The implementation of roleplay teaching method has an effect on the Arabic speaking ability. The proper role play techniques and effectively applied in the process of learning to speak the language of Arabic on a daily basis in accordance with the purpose of learning. The purpose of this method is to increase the activity of learners and educator, so with increasing of student activity has impact to add student achievement and improve the ability to speak Arabic in particular by carrying out appropriate roles activities play a specified theme. Keywords: Ability to speak, Method of Role Playing, Techniques of Teaching Arabic